Steatosis Rates by Liver Biopsy and Transient Elastography With Controlled Attenuation Parameter in Clinical Experience of Hepatitis C Virus (HCV) and Human Immunodeficiency Virus/HCV Coinfection in a Large US Hepatitis Clinic. (1st March 2019) - Sansom, Sarah E; Martin, Jonathan; Adeyemi, Oluwatoyin; Burke, Kerianne; Winston, Crystal; Markham, Sara; Go, Benjamin; Huhn, Gregory
Abstract: Background: Steatosis contributes to liver fibrosis in hepatitis C virus (HCV) and human immunodeficiency virus (HIV)/HCV coinfection. Liver biopsy (LB) is the reference standard for grading steatosis and staging fibrosis, yet recent advances in noninvasive modalities have largely supplanted LB, which may limit recognition of steatosis. We evaluated steatosis rates by LB and transient elastography (TE) with controlled attenuation parameter (CAP) among HCV-infected and HIV/HCV-coinfected patients in a US clinic. Methods: Patients with chronic HCV infection during pretreatment evaluation by LB (n = 421; December 2001 through May 2014) and TE with CAP (n = 1157; May 2016 through May 2017) were included. Fibrosis and steatosis rates by LB and TE with CAP were stratified by HCV versus HIV/HCV coinfection status. Results: Steatosis was not reported in 26.1% of LBs. Moderate to severe steatosis (grade ≥S2) was detected more often with CAP than with LB (in 24.0% vs 11.4% of patients, respectively). Median CAP values were higher in patients with HCV monoinfection than in those with coinfection (230 vs 215.5 dB/m, respectively; P < .001). With TE, the rate of advanced fibrosis (values F3–F4) was higher in HCV monoinfection than in coinfection (25.9% vs 14.8%, respectively; P <.001). With both LB and TE, advanced fibrosis (F3–F4) was significantly associated with moderate to severe steatosis (S2–S3) in HCV monoinfection compared with HIV/HCV coinfection (33.3% vs 4.4%, respectively for LB [ P = 0.003] and 36.0% vs 29.0% for TE [ P = 0.008]). Conclusions: In patients with chronic HCV undergoing liver fibrosis staging, steatosis was detected more often with CAP than LB, with median CAP values higher in HCV monoinfection than HIV/HCV coinfection. Steatosis severity may be increasing in the modern HCV treatment era. Abstract : With both liver biopsy (LB) and transient elastography (TE) with controlled attenuation parameter (CAP), advanced fibrosis was more associated with moderate-severe steatosis in patients with hepatitis C virus (HCV) monoinfection than in those with human immunodeficiency virus (HIV)/HCV coinfection. In patients with chronic hepatitis C undergoing liver fibrosis staging, steatosis was detected more often with CAP than with LB, with median CAP scores higher in HCV monoinfection than in HIV/HCV coinfection. A histopathologic finding of steatosis was not reported in >25% of LBs in this clinical setting. The severity of steatosis may be increasing in the modern HCV treatment era.